Role and Place of Higher Specialized Courts in the Judicial System of Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2020)
The role and place of higher specialized courts in the judicial system of Ukraine have been studied and determined. The author has studied such main categories as “judicial system of Ukraine”, “judiciary”, “judicial system” and “judicial power”. The judicial system of Ukraine has been established. The normative and legal base of functioning of highest specialized courts of Ukraine has been characterized. The author has provided own definition of the categories “judicial system of Ukraine” and “judicial power of Ukraine”.The author has offered to understand the category of “judicial system of Ukraine” as the totality of all hierarchically structured elements of the system (courts), which are endowed with exclusive competence to administer justice, built on the principles of territoriality and specialization, are defined by law and united by general principles of their organization and activity.In turn, the concept of “judicial power of Ukraine” is defined as the activity of courts (judicial system) to administer justice and to perform their professional duties within the limits and in the manner prescribed by the Constitution and laws of Ukraine in accordance with international and legal documents.It has been determined that highest specialized courts in the judicial system of Ukraine are the Supreme Court on Intellectual Property Issues and the Supreme Anti-Corruption Court.It has been concluded that highest specialized courts in the judicial system of Ukraine play an important role in the holistic mechanism of the entire judicial system, since they are endowed with exclusive competence to consider and decide cases on the merits of certain categories, and their activities are determined at the level of a separate regulatory act, which determines their legal status, and hence their place in the judicial system of Ukraine.
Keywords: role; place; significance; higher specialized courts; judicial system; judicial system of Ukraine.